Influence of outpatient rehabilitation on physical efficiency of patients after myocardial infarction - Kielnar, Renata; Janas, Małgorzata; Domka-Jopek, Elżbieta (European Journal of Clinical and Experimental Medicine, 2008)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Infartus cordis is one of the most well-known and the most dramatic form of coronary heart disease also called a heart ischemia. It is characterized by an inadequate blood supply to the heart caused by a significant narrowing of the inside diameter of coronary arteries which provide the heart muscle with blood. A long-lasting physical rehabilitation program adopted individually for each patient is safe and improves the functioning of encircling and central mechanisms. The aim of this research is the evaluation of the influence of clinic cardiological rehabilitation on physical efficiency of male and female patients who suffered from infarctus cordis. ‘83 patients (42 women — 50,6% and 41 men — 49,4%) who suffered from infarctus cordis were examined. The rehabilitation program consisted of 24 one — hour sessions carried out 2-3 times a week. Those sessions included 30 minutes of general keep-fit exercises and 30 minutes of eycloergometer exercise (intervallic training) with the submaximum load individually adjusted to each patient on the basis of the results of stress test. All the time EKG was under control. Rehabilitation lasted about 3 months. The result of the research show better initial tolerance of effort in men (the average load in Wat at the initial training ‘was 57,2 in men and 38,1 in women). The result of the research show that the clinic cardiological rehabilitation significantly increases the level of physical efficiency of patients (the average load between the beginning and the end of the rehabilitation increased about 36% in men and about 42% in women). However the differences in the improvement of physical efficiency based on the sex were not observed. The age did not influence the physical efficiency significantly with the excision of men over 70, whose physical efficiency did not improve substantially after systematic cardiological effort.